Program Hatinya PKK dalam Mendukung Kemandirian Pangan - Agus Nugroho Setiawan; Septi Nur Wijayanti (Universitas Mathla'ul Anwar Banten, 2021)
HATINYA PKK PROGRAM IN SUPPORTING FOOD INDEPENDENCE. A lot of productive land in Kembangarum, Donokerto, Turi, Sleman, DIY is used for the cultivation of salak pondoh, so that the area of land for food and vegetable crops has decreased. There needs to be an alternative land that can be developed for the cultivation of food crops, and one of the potential lands is yards. So far, the yards in Kembangarum have not been used optimally, and are only limited to social interaction, a place to play, a garden or planting less productive plants. To optimize the use of the yard and realize the Hatinya PKK in the Kembangarum, it is necessary to increase the knowledge and skills of members of PKK in managing the yard so that there needs to be guidance in the form of community service. Community service was conducted using several methods, including community education, training, science and technology diffusion, and consultation. The results of the community service show that the Hatinya PKK Program in supporting food safety in Kembangarum were carried out and running well. The community gave positive responses by participating in the activity fully and getting experience and skills in managing the yard, even getting appreciation from the government by being appointed as a representative of the Turi sub-district in the Evaluasi Desa Unggulan Hatinya PKK at Sleman Regency level.